The Relevance of Fiqh Siyasah Dauliyah and Religion as Indonesian Soft Power in International Relations - Damayanti, Rizki (De Jure: Jurnal Hukum dan Syari'ah, 2023)
This study aims to discuss Indonesia's efforts to use moderate Islam as its new identity in global politics, especially after the events of 9/11. One of the Indonesian efforts is pursued through inter-faith and inter-civilizational dialogue. This research is library research with qualitative methods. The approaches used are historical, political, and Islamic perspectives in contemporary international relations studies, namely Fiqh Siyasah Dauliyah. The study results show that there are two main relevancies between the inter-faith and inter-civilizational dialogue with the principles concept of international relations based on fiqh siyasah dauliyah. First, diversity in Islam is stated as part of God's plan for the benefit of mankind. In this context, the various inter-faith and inter-civilizational dialogues organized by Indonesia are necessary conditions for promoting peace, tolerance, harmony, and religious coexistence in the world today. Second, the concept of dialogue between civilizations and between religions is based on the study of textual analysis and historical interpretation of the Al-Quran and As-Sunnah. In this case, the Al-Quran shows various examples of dialogue, one of which is contained in the Al-Quran Surah An-Nahl verse 125 which asks Muslims to show the best courtesy and wisdom when arguing with people of other religions. Keywords: inter-faith dialogue; fiqh siyasah dauliyah; moderate Islam.